The Adaptive Strategies of Kampoeng Batik Laweyan Community in Response to the Late 20th Century Decline in Batik Industry: Strategi Adaptasi Masyarakat Kampoeng Batik Laweyan Pasca Penurunan Industri Batik Akhir Abad 20 - Ilham Cahyo Widodo; Hafizh Maulana Syah Putra (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The decline of Laweyan batik industry in the late 20th century can be attributed to factors such as the advent of printing technology in the 1970s, economic crises, and a lack of generational continuity. The affordability and rapid production of printed batik led to a shift in consumer preference, causing traditional batik to lose its market share. The 1998 monetary crisis further exacerbated the industry's challenges. A crucial aspect was the reluctance of the younger generation to continue the batik tradition, contributing to the decline. The impact reverberated socially and economically, with bankruptcies forcing the sale of iconic Laweyan batik houses. However, the establishment of the Laweyan Batik Village Development Forum (FPKBL) in 2004 marked a strategic effort to revive the industry and promote batik tourism. The community adapted through diversification and tourism initiatives, turning Kampoeng Batik Laweyan into a cultural destination. Local collaboration and harmonious relationships among businesses in Kampoeng Batik Laweyan have played a pivotal role in sustaining both the industry and tourism. This initiative demonstrates that the sustainability of a tourism destination is not solely determined by external factors but also by internal community involvement and cooperation.